1997
DOI: 10.1161/01.atv.17.10.2158
|View full text |Cite
|
Sign up to set email alerts
|

HDL and ApoA Prevent Cell Death of Endothelial Cells Induced by Oxidized LDL

Abstract: We have previously demonstrated that toxic doses of mildly oxidized LDL evokes in cultured cells a delayed and sustained rise of cytosolic [Ca2+], eliciting in turn irreversible cell damage and leading finally to cell death. HDL and delipidated apolipoprotein (apo). A prevented effectively the toxic effect of oxidized LDL to bovine aortic endothelial cells, in a time- and dose-dependent manner. The major part of the protective effect was mimicked by purified apoA-I, whereas purified apoA-II exhibited only very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
2
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 45 publications
6
137
2
3
Order By: Relevance
“…HDL has been demonstrated in vitro to decrease neutrophil degranulation and superoxide production, 32 inhibit LDL oxidation, 33 protect endothelial cells against the effects of oxidized LDL, 34 and prevent the cytokine-induced upregulation of adhesion molecules on endothelial cells, 35 effects that have not been demonstrated to be specifically due to the apoA-I component of the HDL particle. HDL contains a variety of proteins in addition to apoA-I that have been shown to be antiatherogenic in vivo, including apoE, 19,20 apoA-IV, 21,22 LCAT, 23 CETP, 24 and paraoxonase.…”
Section: Discussionmentioning
confidence: 99%
“…HDL has been demonstrated in vitro to decrease neutrophil degranulation and superoxide production, 32 inhibit LDL oxidation, 33 protect endothelial cells against the effects of oxidized LDL, 34 and prevent the cytokine-induced upregulation of adhesion molecules on endothelial cells, 35 effects that have not been demonstrated to be specifically due to the apoA-I component of the HDL particle. HDL contains a variety of proteins in addition to apoA-I that have been shown to be antiatherogenic in vivo, including apoE, 19,20 apoA-IV, 21,22 LCAT, 23 CETP, 24 and paraoxonase.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are common features of CKD and promote endothelial cell injury and apoptosis. Acting via its constituent ApoA-1 and sphingosine-1 phosphate (S1P) proteins, HDL lowers caspase-3 activity, inhibits the formation of ROS, and prevents apoptosis of endothelial cells [22][23][24] . In addition, normal HDL facilitates the repair, migration, and proliferation of endothelial cells and increases the number of circulating endothelial progenitor cells -events that are essential for vascular repair and prevention of plaque formation [25][26][27] ( FIG.…”
Section: Biologic Functions Of Normal Hdlmentioning
confidence: 99%
“…The situation is completely different in atherosclerotic plaques, in a high oxidative stress environment where macrophages produce high amounts of nitric oxide or peroxynitrite that could induce apoptotic cell death (Kockx and Herman 2000). In the aorta the capacity of HDL to quench endothelial cell apoptosis may therefore represent an antiatherogenic property of HDL (de Souza et al 2010;Nofer et al 2001;Suc et al 1997;Sugano et al 2000). HDL has been shown to attenuate endothelial cell apoptosis induced by different stimuli such as TNF-α, oxLDL, and growth factor deprivation (de Souza et al 2010;Nofer et al 2001;Suc et al 1997;Sugano et al 2000).…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%
“…In the aorta the capacity of HDL to quench endothelial cell apoptosis may therefore represent an antiatherogenic property of HDL (de Souza et al 2010;Nofer et al 2001;Suc et al 1997;Sugano et al 2000). HDL has been shown to attenuate endothelial cell apoptosis induced by different stimuli such as TNF-α, oxLDL, and growth factor deprivation (de Souza et al 2010;Nofer et al 2001;Suc et al 1997;Sugano et al 2000). It has been suggested that HDL may inhibit both death-receptor and mitochondrial-mediated apoptotic pathways.…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%